Exploring Students’ Preferences on a Teacher’s Written Feedback in a High School Context - Yessi Widyasari; Gita Rahmi; Yella Dezas Perdani (Jurnal Ilmiah Multidisiplin, 2025)
Since writing involves complex rules, teachers’ written feedback plays a crucial role. However, students are sometimes dissatisfied because they do not fully understand teachers’ expectations. This study investigates high school students’ preferences regarding the focus and strategy of teachers’ written feedback, emphasizing differences between high and low achievers. Using a qualitative case study design, data were collected through document analysis and semi-structured interviews with one English teacher and nine third-grade students at a senior high school in Bandung, West Java. The findings indicate that students’ language proficiency did not affect their preferences. Both high and low achievers favored form-focused feedback—particularly grammar, vocabulary, and mechanics—over content-focused feedback, influenced by their grammatical difficulties and the teacher’s feedback style. They also preferred indirect feedback strategies, such as underlining, symbols, and codes, because these methods promote self-correction, reflective learning, and long-term retention. However, some students struggled to interpret codes and occasionally appreciated direct feedback. The study highlights the need to balance form- and content-focused feedback and to combine direct and indirect strategies to address diverse learning needs. These findings enhance understanding of students’ feedback preferences in the high school EFL context, offering insights for teachers to design more effective and meaningful feedback.